Grid Computing: The Sawy Managers Guide - Plaszczak (Pawel); Wellner (Richard) ("17-A / 1, Main Ring RoadLajpat Nagar IV,New Delhi,New Delhi,India-110 024", 2006)
Distributed Computing
22.5
Keywords: Distributed Computing